Assessing the threats facing wetland mammals in India using an evidence‐based conservation approach. (23rd February 2021) - Chatterjee, Arnab; Bhattacharyya, Sabuj
Abstract: Environmental change and anthropogenic pressure are primary drivers of biodiversity loss, particularly in wetland ecosystems that have been modified significantly. Among wetland specialists, mammals may be particularly vulnerable to extinction. We aimed to increase understanding of threats and knowledge gaps faced by 11 mammal species inhabiting wetlands throughout India. We adopted a systematic literature search protocol following an evidence‐based conservation approach to obtain information on conservation threats and identify knowledge gaps for each species. Each species received threat scores based on the occurrence and magnitude of ecological and anthropogenic threats, a score based on its International Union for Conservation of Nature (IUCN) Red List category, and a knowledge gap score. A cumulative conservation threat score based on the four individual scores was calculated for each species to assess overall conservation threats. Only about 10% of the literature search results were relevant. Of the major research categories, ecology was the most well‐studied, whereas the impact of anthropogenic pressure on wetland mammals was the least studied. Pressing ecological and anthropogenic threats, scientific knowledge gaps, and conservation needs contributed to a high cumulative threat score for the sangai Rucervus eldii eldii (cumulative threat score = 34), followed by the wild Asian buffalo Bubalus arnee (threat score = 33) and the Bengal marsh mongoose Herpestes palustris (threat score = 32). Poaching/hunting, habitat loss due to development, and changes in land‐use practices were found to be the major anthropogenic threats resulting in decreasing population trends. We identified knowledge gaps concerning the ecology of wetland mammals (e.g. population abundance). It is essential that these knowledge gaps are filled for effective conservation planning. We identified important areas (population ecology, disease ecology, human–wildlife conflict, changes in land use) that should be considered as research priorities for wetland mammals in India, in order to make conservation efforts more effective and enable management planning, to ensure the long‐term survival of these mammals. Abstract : We adopted a systematic literature search protocol following an evidence‐based conservation approach to obtain information on conservation threats and identify knowledge gaps for eleven wetland mammals in India. We reviewed 979 documents and each species received threat scores based on the occurrence and magnitude of ecological and anthropogenic threats, a score based on its International Union for Conservation of Nature (IUCN) Red List category, and a knowledge gap score. A cumulative conservation threat score based on the four individual scores was calculated for each species to assess overall conservation threats. Pressing ecological and anthropogenic threats, scientific knowledge gaps and conservation needs contributed to a high cumulative threat score for the sangai, wild Asian buffalo, and the Bengal marsh mongoose. Poaching/hunting, habitat loss due to development, and changes in land‐use practices were found to be the major anthropogenic threats resulting in decreasing population trends. We identified important areas (population ecology, disease ecology, human–wildlife conflict, changes in land use) that should be considered as research priorities for wetland mammals in India, in order to make conservation efforts more effective and enable management planning, to ensure the long‐term survival of these mammals. Zusammenfassung auf Deutsch: Umweltveränderungen und anthropogener Druck sind Haupttreiber für den Verlust der biologischen Vielfalt, insbesondere in Feuchtgebieten, die erhebliche ökosystemare Veränderungen erfahren haben. Unter den Feuchtgebietsspezialisten sind Säugetiere möglicherweise besonders vom Aussterben bedroht. Ziel unserer Studie war es, das Verständnis von Bedrohungen und Wissenslücken für 11 Säugetierarten in Feuchtgebieten Indiens zu verbessern. Wir haben eine systematische Literaturrecherche anhand von evidenzbasierten Schutzansätzen durchgeführt, um Informationen über Bestandsbedrohungen zu erhalten und Wissenslücken für Arten zu identifizieren. Jede Art erhielt Gefährdungsbewertungen basierend auf dem Auftreten und dem Ausmaß ökologischer und anthropogener Bedrohungen, eine Bewertung auf Grundlage der Roten Liste der Internationalen Union für Naturschutz (IUCN) sowie eine Bewertung der Wissenslücken.Für jede Art wurde eine kumulative Bewertung der Schutz Bedrohung basierend auf den vier Einzelbewertungen berechnet, um die Gesamtbedrohungen für die Erhaltung zu bewerten. Nur etwa 10% der Ergebnisse der Literaturrecherche waren relevant. Von den wichtigsten Forschungskategorien war die Ökologie am besten untersucht, der Einfluss des anthropogenen Drucks auf Säugetiere in Feuchtgebieten am wenigsten. Der ökologische und anthropogene Gefährdungsdruck, wissenschaftliche Wissenslücken und Schutzbedürftigkeit trugen zu einem hohen kumulativen Gefährdungswert für den Sangai Rucervus eldii eldii (kumulativer Gefährdungswert = 34) bei, gefolgt vom wilden asiatischen Büffel Bubalus arnee (Gefährdungswert = 33) und dem Bengalischer Sumpfmungo Herpestes palustris (Gefährdungswert = 32) bei. Wilderei/Jagd, Verlust des Lebensraums aufgrund der regionalen Entwicklung sowie Änderungen der Landnutzung erwiesen sich als die größten anthropogenen Bedrohungen, die zu negativen Trends der Populationsentwicklung führten. Wir konnten Wissenslücken hinsichtlich der Ökologie von Säugetieren der Feuchtgebiete (z.B. Bestandszahlen) identifiziert. Für die Entwicklung von effektiven Schutzstrategien müssen diese Wissenslücken geschlossen werden. Wir haben wichtige Gebiete (Populationsökologie, Krankheitsökologie, Mensch–Wildtier Konflikt, Landnutzungsänderungen) identifiziert, die als Forschungsprioritäten für Säugetiere der Feuchtgebiete in Indien betrachtet werden sollten, um die Schutzbemühungen effektiver zu gestalten und eine Managementplanung zu ermöglichen, die ein langfristiges Überleben dieser Säugetiere sichert.